Comparative analysis of methods for determining the air objects’ coordinates using wide-area multilateration systems - Svyd, I.V.; Semenets, V.V.; Maltsev, O.S.; Tkach, M.G.; Starokozhev, S.V.; Datsenko, O.O.; Shevtsov, I.O. (Radiotekhnika, 2022)
The presented work considers the place and role of wide-area multi-position airspace surveillance in the information support of airspace control and air traffic control systems. Classification of methods for estimating the coordinates of air objects using various primary measurements of the parameters of received signals in multi-position observation is given. A quantitative assessment of the accuracy in determining the air objects’ coordinates by the considered methods is also given. The capabilities of wide-area multi-position surveillance systems increase significantly when using the principles of constructing a secondary surveillance radar as a non-synchronous network, and an aircraft responder as an open single-channel queuing system with servicing the first correctly received request signal. An unauthorized request from an aircraft responder makes it possible to switch from completely passive methods for detecting and determining the coordinates of an air object to active-passive ones, which provide an increase in the accuracy of solving a coordinate task by dozens of times while maintaining the energy secrecy of a wide-area multi-position observation system. It is shown that the use of active and passive methods for constructing wide-area multi-position observation systems makes it possible to implement goniometric, difference-range, goniometer-range, total-range and goniometer-total-range methods for determining the coordinates of an air object. This increases significantly the number of options for estimating the coordinates of an air object. As a result, it allows improving the quality of information support for users by choosing the optimal method for estimating the coordinates of the observed air objects using various primary measurements of the received signals parameters.